Passengers Satisfaction Analysis of Quality and Schedule of Commuter Line Service: A Case Citayam-Tebet Route - Fauziawati, Rizky; Rifai, Andri Irfan; Handayani, Susanty (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Commuter Railways (KRL) is one of Indonesia's modes of mass transportation, especially in the Jabodetabek area. The existence of KRL makes it easier for people to travel, so it is necessary to emphasize service quality in following its users' wishes. This paper aims to increase KRL user satisfaction with KRL services and schedules. Questionnaires were distributed to 100 respondents at the station and on the KRL. The data analysis method used is the Importance Performance Analysis method which is processed using Microsoft Excel. From the analysis results, nine variables are considered essential but still need to meet the expectations of KRL users, so they become the top priority. Then, seven variables are considered essential and have met expectations, so these variables must be improved. Based on the research results on the level of passenger interest in the Citayam-Tebet KRL route, an average value of 4.60 is obtained with an average level of performance of 4.11, which means that the variable is still not as expected and does not meet the satisfaction of KRL passengers.